An Empirical Study on Product Quality and Competitive Pricing as Key Factors for Business Success - Mersiana Setiarini; Christy Christy; Sutomo Sutomo (International Journal of Management Science and Information Technology, 2025)
This study examines the impact of product quality and competitive pricing on business success in the retail sector. A quantitative approach was employed with a survey design to collect data from 200 business owners in Jakarta a structured questionnaire measured product quality, competitive pricing, and business success. Multiple linear regression analysis assessed the relationship between the two independent variables and business success as the dependent variable. The analysis results show that product quality significantly influences business success, with a regression coefficient of 0.542, indicating that an increase of one unit in product quality will improve business success by 54.2%. Meanwhile, competitive pricing also positively impacts business success, with a coefficient of 0.318. The p-values for both variables are less than 0.05, indicating their effects are statistically significant. The regression model generated an adjusted R² value of 0.645, meaning that product quality and competitive pricing explain 64.5% of the variation in business success. Hypothesis testing confirms that both variables have a positive impact, with product quality having a more significant effect. These findings suggest that retail businesses need to enhance their product quality and set competitive prices to succeed in a competitive market. This study provides insight into the role of these two factors in achieving better business performance. Fire extinguishers, eyewashes, a first aid kit, a balance board, and a smoke detector will support the hazardous waste collection centre facility.